Changes in the structure of employment and the discussion on occupational polarization in Latin America the cases of Argentina, Chile and Mexico - Roxana Maurizio; Ana Paula Monsalvo; Sol Catania; Silvana Martínez (European Commission, Joint Research Centre (JRC), 2023)
This article examines the changes in the structure of employment and income in three Latin American countries -Argentina, Chile and Mexico- during different subperiods over the first two decades of the new millennium. It applies the "jobs approach", which combines occupation type and branch of activity. The study is carried out for all workers and also for different subgroups defined on the basis of gender, age, educational level and formality status. The results show a wide variation of structural change patterns between periods and countries. In Argentina, an inverted U-shaped pattern is found in employment growth for the period 2003-12, while a certain polarizing trend is observed between 2012 and 2019. In Chile, no clear pattern is identified between 2000 and 2009, and a certain pattern of upgrading is found from 2009 until 2017. In Mexico, there is no evidence of significant changes between 2006 and 2010, while an inverted U-shaped pattern is found in the following decade. In the three countries, when the nearly two decades under analysis are considered as a whole, a reallocation of jobs from the lower end of the distribution to jobs in the middle and upper part of the distribution can be observed. Lastly, mean wages behaved differently from what was observed in jobs, as lower-income occupations experienced greater increases during the period studied.
Keywords: 330; job polarization; structural change; jobs; Latin America